The delivery and transmembrane transport mechanism of SVCV nanovaccine - Han Zhang; Pan-pan Zhang; Xin-Xin Liu; Hai-hua Peng; Qun Liu; Jun Wang; Bin Zhu; Yong-Can Zhou; Yun Sun; Chen Zhang (Nano TransMed)
Spring viremia of carp virus (SVCV) is a fatal microorganism for a variety of cyprinid fish species, sparking off enormous economic losses in freshwater fish aquaculture. For alleviating losses, immersion vaccination is an extremely promising maneuver to prevent and curb on SVCV infection. In our previous research, we designed a modular immersion nanovaccine (LSG-TDH) targeting SVCV, and found that it could induce not merely mucosal immunity but systemic immune responses in zebrafish. Nevertheless, our previous research was unable to elaborate on how LSG-TDH were taken up by the cells. Thereby, this study aimed to investigate its transmembrane transport mechanism in vitro using epithelioma papulosum cyprini (EPC) cells and macrophages as models. The transmembrane transport mechanism of LSG-TDH on EPC cells and macrophages was analyzed by cell fluorescence, flow cytometry and chemical inhibitor experiments. The results showed that the entry of LSG-TDH into cells was time-dependent and energy-dependent. Chlorpromazine significantly inhibited the transmembrane transport of LSG-TDH. The contents of LSG-TDH into EPC cells and macrophages after treated with chlorpromazine decreased by 80 % and 71 %, respectively. It is indicated that the transmembrane transport of LSG-TDH was mainly achieved through clathrin-mediated endocytosis pathway. This study provides a reference for the delivery mechanism of aquatic nanovaccine, which has important scientific significance and application prospect.